Greenhouse gas dynamics in river networks fragmented by drying and damming - Silverthorn, Teresa; López‐Rojo, Naiara; Foulquier, Arnaud; Chanudet, Vincent; Datry, Thibault (Freshwater biology, 2023)
River fragmentation by drying and damming is occurring more frequently in the Anthropocene era, yet there is limited knowledge of how this fragmentation influences greenhouse gas (GHG) fluxes in river networks. River networks have the potential to be important sources of GHGs to the atmosphere through both similar and dissimilar mechanisms associated with temporary (drying) and permanent (damming) fragmentation. We conducted a review of the literature and found 49, 43 and six studies about GHGs (CO 2 , CH 4 and N 2 O) in rivers impacted by damming, drying and their interaction, respectively. We found research lacking in non‐arid climates and in small water‐retention structures for studies regarding drying and damming, respectively. The major factors directly influencing GHG fluxes in river networks impacted by drying were sediment moisture, temperature, organic matter content and texture. In networks impacted by damming, the most influential factors were water temperature, dissolved oxygen, and phytoplankton Chlorophyll‐ a . Based on our literature review and meta‐ecosystem theory, we propose that the spatial distribution of fragmentation strongly influences GHG fluxes at the river‐network scale. The actionable future research directions identified here will help to improve our understanding of the effects of fragmentation by drying and damming on GHG fluxes, with the potential to inform river management and climate change mitigation strategies.